PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH PADA MATA PELAJARAN PAI KELAS 5 SD TEMA MARI MENGENAL RASUL-RASUL ALLAH SWT - Wardani Wardani; Rahwan Rahwan; Ach. Zukin (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
This research aims to 1) produce the learning media development product based macromedia flash on the subject matter of Islamic religion education by theme “let’s get to know the prophets of Allah” class 5th SDN 2 Sumberanyar that is worthy of being reviewed from the assessment of media experts and material experts; 2) knowing the response of students' motivation to the development of learning media products based on macromedia flash. The research method used in this research is research and development by several steps including 1) potential and problems; 2) data collection; 3) product design; 4) expert validation; 5) design revision; 6) field trials. The subject of this research are 20 students of class 5th SDN 2 Sumberanyar. The results of this research show that 1) the product of developing macromedia flash-based learning media in the subject of Islamic religious education by the theme "Let's Get to Know Allah's Prophets" for grade 5th Elementary School is categorized as "very decent" with each score obtained from media expert and material expert by 95.2% and 98.2%; 2) The response of students is very excellent to the product of this macromedia-based learning media development with a percentage of 85.9% and learning motivation indicators getting a score of 92.